The Effect of Integrated Marketing Communication on Product and Cooperative Performance: A Case Study of an Agricultural Development Cooperative (Third Sector Social Economic Review, 2026)
This study aims to examine the effects of integrated marketing communication (IMC) activities on product performance and cooperative performance within the context of third sector organizations. In today's environment, where social economies are gaining increasing global significance, the sustainability of cooperatives depends not only on improving their production processes but also on their ability to develop effective communication, branding, and digital marketing strategies. Within this scope, the study analyzes the contribution of IMC to product and cooperative performance and investigates whether participants’ perceptions vary across demographic variables.The research was conducted using a relational survey model within a quantitative research framework. Data were collected through face-to-face questionnaires from 348 producers who are members of the S.S. Çamönü Agricultural Development Cooperative operating in the Akhisar district of Manisa province. The dataset consists of the Integrated Marketing Communication Scale from the literature, along with Product Performance and Cooperative Performance scales developed by the researcher. Validity and reliability analyses were performed, and t-tests, ANOVA, correlation, and regression analyses were conducted using SPSS 24.0.The findings indicate that integrated marketing communication has a significant and positive effect on both product performance and cooperative performance. In addition, participants’ perceptions of marketing communication, product performance, and cooperative performance differ significantly according to various demographic characteristics. These results reveal that the sustainability and competitiveness of cooperatives are associated not only with production capacity but also with the effectiveness of integrated marketing communication practices. Accordingly, the study emphasizes that communication, branding, and digital marketing-oriented strategies are essential for cooperatives operating within the social economy to achieve sustainable development goals.
Keywords: Integrated Marketing Communication; Product Performance; Cooperative Performance; Social Economy; Brand